Implementasi Kecerdasan Buatan untuk Memantau Lahan Pertanian - Setiany, Anggit Prastika; Noviyanto, Dian; Irfansyahfalah, Muhammad; Aisah, Siti; Yulianti, Yulianti; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
This researcher is planning on agriculture monitor system effective and planting will increase harvest yield. Effort to do a plan and construction in this agriculture, could give benefits in-between to knows   neighborhood condition with appropriate plant type in environtment of agriculture land and give various information. This system an AI implememtation which use technology like IoT, and use Farming System Analysis matriks variable in agriculture field which is related like, soil, plant, animal, tools, labor, capital, up to agriculture effort. Because the technology has not been developed this time and still got a problem and lack on agriculture sector, one of them is hard to choose a good land so that affect the farmers's harvest result. The results of this study indicate that the application of artificial intelligence can facilitate the community in farming and provide useful information ranging from planting to harvesting and reducing failure in harvesting, besides that other benefits provided are that the food needs of farmers can be fulfilled and even marketed.